From active play to sedentary lifestyles: understanding the decline in physical activity from childhood through adolescence—a systematic review - Habyarimana, Jean de Dieu; Tugirumukiza, Etienne; Sun, He; Pathirana, Amith; Zhou, Ke (Frontiers in Public Health, 2025)
The decline in physical activity (PA) from childhood through adolescence is an escalating global concern with far-reaching implications for health and wellbeing. While prior research has examined general PA trends, critical gaps remain regarding the precise onset of decline, contributing factors, and the most effective intervention strategies. This systematic review synthesizes evidence on: (a) the age or developmental stage at which PA levels significantly decline, (b) key factors influencing this decline, and (c) interventions shown to be effective in slowing or preventing it. A comprehensive search was conducted across four electronic databases: Scopus, Web of Science, Google Scholar, and CORE guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. From an initial pool of 14,621 records, 34 studies met the inclusion criteria. Findings reveal that PA levels begin to decline as early as age 7, with the most substantial drop occurring around age 9. Modifiable factors such as self-efficacy, motivation, screen time, and academic workload emerged as key contributors to this trend. Among intervention strategies, school-based, multicomponent, and theory-driven approaches, particularly those incorporating autonomy-supportive teaching, addressing both PA and sedentary behaviors, and engaging multiple stakeholders, demonstrated the strongest effectiveness. These results underscore the urgent need for early, multidimensional interventions to sustain PA engagement across developmental stages. Stakeholders including schools, policymakers, and researchers should prioritize integrated PA promotion strategies to reverse early inactivity trends. Future research should focus on the long-term sustainability of these interventions beyond the school context to ensure enduring behavioral change.